Non-pulsed Sinusoidal Electromagnetic Field Rescues Animals From Severe Ischemic Stroke via NO Activation - Font, Lena P.; Cardonne, Miriam M.; Kemps, Hannelore; Meesen, Raf; Salmon, Oneida F.; González, Fidel G.; Lambrichts, Ivo; Rigo, Jean-Michel; Brône, Bert; Bronckaers, Annelies (Frontiers in Neuroscience, 2019)
Despite the high prevalence and devastating outcome, only a few treatment options for cerebral ischemic stroke exist. Based on the nitric oxide (NO)-stimulating capacity of Non-Pulsed Sinusoidal Electromagnetic Field (NP-SEMF) and the possible neuroprotective role of NO in ischemic stroke, we hypothesized that NP-SEMF is able to enhance survival and neurological outcome in a rat model of cerebral ischemia. The animals in which ischemic injury was induced by occlusion of both common carotid arteries, received daily 20 minutes NP-SEMF of either 10 or 60 Hz for 4 days. NP-SEMF dramatically increased survival, reduced the size of the infarcted brain area and significantly improved the neurological score of the surviving rats. Corresponding to previous reports, NP-SEMF was able to induce NO production in vitro. The importance of NO as a key signaling molecule was highlighted by inhibition of the NP-SEMF beneficial effects in the rat stroke model after blocking NO synthase (NOS). Our results indicate for the first time that NP-SEMF exposure (13.5mT at 60 Hz and 10 Hz) improves the survival and neurological outcome of rats subjected to cerebral ischemia and that this effect is mediated by NO, underlining the great therapeutic potential of NP-SEMF as therapy for ischemic stroke.